Pertanggung Jawaban Pidana Dalam Perkara Ilegal Mining Pada Peradilan Negeri Marisa - Fransisko Ngajow, Malfrid Frangky; Kadir, Yusrianto; Moonti, Roy Marthen; Kasim, Muslim (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The purpose of the research is to know and analyze the criminal liability of the perpetrator in the case of illegal mining in the Marisa District Court of Pohuwato Regency has been in accordance with the objectives of the law (certainty, benefit, and justice) and to know and analyze the factors that influence the consideration of judges in examining, adjudicating, and deciding cases of illegal mining in the Marisa District Court of Pohuwato Regency. The type of research used in this legal writing is socio-juridical legal research. Criminal responsibility of the perpetrator in illegal mining cases is very important to maintain legal certainty, expediency, and justice. Courts need to ensure that perpetrators are given sanctions appropriate to the level of offense they commit and that the sanctions are effective in preventing similar acts in the future. In addition, fair and proportional treatment of perpetrators must also be ensured to maintain the integrity of the justice system and the judge's consideration in deciding Case No. 37/Pid.Sus/2023/PN Mar was in accordance with Article 184 of the Criminal Procedure Code, namely based on legal facts, witness testimony, testimony of the defendant and instructions in the form of evidence, so that the judge's consideration in his verdict had fulfilled the elements and conditions of the defendant's conviction.